Improving Responsibility and Mathematical Critical Thinking of Grade IV A Students of SDN Kentungan Through Contextual Learning Model - Alip Tripambudi; Christiyanti Aprinastuti; M.M. Suyatini (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2021)
The background of this research was the low responsibility and low mathematical critical thinking of fourth-grade students of SDN Kentungan in. This study aimed to: 1) describe efforts to improve the students' responsibility and critical thinking through the application of a contextual learning model; 2) improve the responsibility of fourth-grade students through the application of contextual learning models; 3) improve the critical thinking of fourth-grade students through the application of contextual learning models. The type of this research was Classroom Action Research (CAR). The subjects of this study were 24 grade IVA students of SDN Kentungan in the 2020/2021 Academic Year. The object of this research was to improve the students’ responsibility and critical thinking. The instruments used in this study were questionnaires and observation sheets. The data analysis technique was descriptive quantitative. The results showed that: 1) Efforts to increase students' responsibility and critical thinking have been successfully carried out by using the contextual learning model through the following steps; a) Relating, b) Experiencing, c) Cooperating, d) Applying, e) Transfering. 2) The application of a contextual learning model improved the students’ responsibility. It could be seen from the increase in the average score for the initial conditions of 53,3% (less responsible). In the first cycle, it increased to 60.3% (Sufficiently Responsible). Then, in the second cycle, it increased to 73.5% (responsible). 3) The application of a contextual learning model improved the students' critical thinking. It could be seen from the increase in the initial condition average score of 56.2% (less critical). In the first cycle, it increased to 60.1% (quite critical), and in the second cycle, it increased to 71.85% (critical).